The Chaebol’s contribution on South Korea nation branding through Korean wave - Sarah Dannita; Shannaz Deniar (Universitas Muhammadiyah Malang, 2021)
Korean Wave atau yang dikenal dengan Hallyu Wave menjadi salah satu ciri nation branding dari Korea Selatan. Sebagai sebuah kebutuhan dari negara untuk memperkuat eksistensinya, kajian mengenai nation branding menjadi menarik untuk melihat bagaimana strategi yang dipilih dari aktor negara serta bagaimana bentuk kolaborasi yang mereka lakukan. Penelitian ini menelaah kontribusi Chaebol dalam penguatan nation branding melalui Korean Wave. Dengan menggunakan Nation Branding Index oleh Simon Anholt, penelitian ini melihat bagaimana bentuk kontribusi dan kolaborasi antar aktor dalam enam index, yakni national governance, export promotion, tourism, investment and immigration, cultural/heritage relations, dan public/ people. Hasil penelitian ini memperlihatkan usaha Chaebol melalui kerjasama, joint venture, produksi, distribusi, serta promosi konten-konten dalam hallyu terlihat berdampak signifikan baik dalam citra promosi maupun pemasaran produk kepada masyarakat internasional. The Korean Wave, also known as the Hallyu, is one of the nation branding’s characteristics of South Korea. As a need from the state to strengthen its existence, the study of nation branding is interesting to see how the strategies chosen by state actors are and what forms of collaboration they take. This study will examine the contribution of Chaebol in strengthening nation branding through the Korean Wave. By using the Nation Branding Index by Simon Anholt, this study looks at the forms of contribution and collaboration between actors in six nation branding indexes, namely national governance, export promotion, tourism, investment and immigration, cultural/heritage relations, and public/people. The results of this study show that Chaebol's strategies through cooperation, joint ventures, production, distribution, and promotion of hallyu content has a significant impact both in image promotion and product marketing to the international community towards South Korea.